Recycling method of waste lithium ion battery
By using the liquid first Ga-based alloy to separate the aluminum foil and the positive electrode active material in the waste lithium-ion battery, the aluminum residue problem is solved, and by preparing high-entropy alloy nanoparticle catalyst, the application of materials and the recycling efficiency of resources are expanded.
Patent Information
- Application Number
- CN202510421188.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-07
AI Technical Summary
The prior art is difficult to completely remove aluminum residue when separating aluminum foil from the cathode active material in waste lithium-ion batteries, which increases the difficulty of subsequent recycling processes and limits the application range of cathode active materials.
The liquid first Ga-based alloy (such as GaSn alloy) is used to contact the positive electrode sheet of the used lithium-ion battery at room temperature. The high wettability and corrosion of Ga atoms are used to achieve rapid, pollution-free and low energy-consuming separation of aluminum foil and positive electrode active material. At the same time, a high-entropy alloy nanoparticle catalyst was prepared using the separated positive electrode active material and negative electrode copper foil.
The separation of positive electrode active materials without aluminum residues has been achieved, the application range of materials has been expanded, and the recycling efficiency and catalytic activity of resources has been improved through the preparation of high-entropy alloy nanoparticle catalysts.
Smart Images

Figure CN119921019A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling and regenerating waste lithium-ion batteries, and in particular relates to a method for recycling and reusing waste lithium-ion batteries. Background Art
[0002] At present, the recycling and reuse of waste lithium-ion batteries has become a key area of resource recycling and environmental protection. Among them, waste lithium-ion batteries contain abundant high-value metals, such as lithium, cobalt and nickel. The recycling of these metals not only helps to alleviate the problem of resource shortage, but also reduces the potential harm to the environment. In addition, the positive electrode and negative copper foil of waste lithium-ion batteries are also important recyclable materials. The positive electrode contains aluminum foil and positive electrode materials. Among them, the positive electrode material is a carrier of high-value metal resources, and its efficient separation and recycling is a key link in resource recycling.
[0003] At present, the separation methods of aluminum foil and positive electrode active materials mainly include heat treatment, organic solvent dissolution and chemical corrosion of aluminum foil with mineral acid. Among them, the heat treatment method decomposes the binder at high temperature to reduce the bonding force between the active material particles, thereby weakening the adhesion between the active material layer and the aluminum foil, and realizing the separation of the positive electrode active material and the aluminum foil. The organic solvent dissolution method is to use an organic solvent with good solubility to treat the positive electrode sheet so that the positive electrode active material falls off the aluminum foil. The chemical corrosion method of aluminum foil with mineral acid is to use mineral acid to dissolve the aluminum foil to achieve rapid separation of the aluminum foil and the active material.
[0004] However, the above separation methods inevitably introduce aluminum residues into the separated positive electrode active materials, which not only increases the difficulty of subsequent recycling processes, but also limits the application scope of positive electrode active materials in waste lithium-ion batteries.
[0005] In addition, existing technologies mainly focus on the recovery of single metals from waste lithium-ion batteries, which makes it difficult to fully tap the potential value of positive electrode active materials and limits the application of positive electrode active materials in waste lithium-ion batteries. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for recycling waste lithium-ion batteries.
[0007] The present invention realizes the rapid, pollution-free and low-energy separation of the aluminum foil and the positive electrode active material layer by utilizing the property that the first Ga-based alloy can remain in a liquid state at room temperature and the high wettability of the first Ga-based alloy to the aluminum foil; based on the separated positive electrode active material, in combination with the negative electrode copper foil and the second Ga-based alloy, a synthesis method of a high entropy alloy nanoparticle catalyst is developed, which solves the problem of aluminum residue in the positive electrode active material separated in the prior art and expands the application of the positive electrode active material.
[0008] The first object of the present invention is to provide a method for recycling waste lithium-ion batteries, comprising the following steps: Separate the positive electrode sheet and negative electrode copper foil from waste lithium-ion batteries.
[0009] The separated positive electrode plate is immersed in a liquid first Ga-based alloy to separate the aluminum foil from the positive electrode material, and the separated positive electrode material is calcined to obtain a positive electrode active material; the liquid first Ga-based alloy is a GaSn alloy; the mass percentage of Ga contained in the liquid first Ga-based alloy is 85% to 90%.
[0010] The positive electrode active material is used as raw material, and regenerated positive electrode plates are prepared after regeneration, and then assembled to prepare regenerated lithium-ion batteries.
[0011] Alternatively, a high entropy alloy nanoparticle catalyst is prepared using negative electrode copper foil, positive electrode active material and a liquid second Ga-based alloy as raw materials; the liquid second Ga-based alloy is a GaIn alloy.
[0012] It should be noted that in order to prevent the waste lithium-ion batteries from short-circuiting or spontaneously igniting during the treatment process, the present invention uses salt water immersion to discharge the waste lithium-ion batteries until the voltage drops to 0V; then the positive electrode sheet and the negative electrode copper foil are taken out by manually disassembling the battery packaging.
[0013] It should also be noted that the first Ga-based alloy is a eutectic alloy that is liquid at room temperature and has excellent metal wettability and high activity. When the first Ga-based alloy comes into contact with the aluminum foil in the positive electrode plate, the fluid first Ga-based alloy can quickly spread on the surface of the aluminum foil and penetrate into the microscopic cracks, destroying the original aluminum oxide protective layer on the surface of the aluminum foil. At the same time, since the Ga atoms in the first Ga-based alloy have high wettability to the aluminum foil, the Ga atoms can directly contact the aluminum foil matrix. Ga atoms preferentially diffuse along the grain boundaries of the aluminum foil, weakening the grain boundaries, leading to the fracture and disintegration of the aluminum foil structure; the grains of the aluminum foil are gradually dissolved after being eroded by Ga atoms, and the surface of the aluminum foil becomes powdery or porous, obtaining the positive electrode active material, thereby realizing the rapid separation of the aluminum foil and the positive electrode active material.
[0014] Preferably, the mass percentage of Ga contained in the liquid first Ga-based alloy is 85% to 90%; more preferably, the mass percentage of Ga contained in the liquid first Ga-based alloy is 87.5%. This is because when there is too much or too little Ga, Ga or other metals in the first Ga-based alloy will precipitate at room temperature, causing waste.
[0015] Preferably, the GaSn alloy is prepared by the following method: Ga and Sn are mixed and heated under vacuum conditions to obtain the GaSn alloy; the heating temperature is 300° C. Ga can be made into liquid and synthesize the GaSn alloy with Sn.
[0016] In order to ensure that the aluminum foil in the positive electrode plate reacts completely with the GaSn alloy after contact, preferably, the immersion time is 30 min to 35 min.
[0017] Preferably, the calcination temperature during separation of the positive electrode active material is 600° C. and the calcination time is 4 h to 6 h, so as to ensure that the graphite and binder in the positive electrode material are completely reacted and removed.
[0018] The present invention uses negative electrode copper foil, positive electrode active material and liquid second Ga-based alloy as raw materials to prepare high entropy alloy nanoparticle catalyst. High entropy alloy nanoparticle catalyst has a high specific surface area and unique catalytic activity, thus playing an important role in the field of organic liquid flow battery catalysis and nitrate reduction catalysis. Through this recycling and reuse method, the present invention allows the positive electrode material and negative electrode copper foil of waste batteries to be recycled, which not only reduces the environmental burden of electronic waste, but also provides a new way for the green synthesis of catalysts.
[0019] Preferably, the specific method for preparing the high entropy alloy nanoparticle catalyst is: The separated negative electrode copper foil and the liquid second Ga-based alloy are dissolved in a solvent and crushed to obtain a nanoparticle solution; the nanoparticle solution is evenly mixed with the positive electrode active material to obtain a precursor solution; the precursor solution is placed on carbon paper and pulse-heated in a vacuum environment to obtain a high-entropy alloy nanoparticle catalyst.
[0020] It should be noted that the liquid second Ga-based alloy is a GaIn alloy. The Ga atoms in the GaIn alloy have a relatively negative mixing enthalpy with the Cu atoms in the copper foil, and the Co atoms and Fe atoms in the positive electrode active material, which makes the atoms tend to be affinity; at the same time, the liquid GaIn alloy has high diffusivity and can react quickly with other metal atoms; and at high temperatures, this diffusion will accelerate the mixing of metal atoms, creating conditions for the formation of high entropy alloys.
[0021] Preferably, the GaIn alloy is prepared by the following method: Ga and In are mixed and heated under vacuum conditions to obtain the GaIn alloy.
[0022] Preferably, the mass percentage of Ga contained in the GaIn alloy is 70% to 80%; more preferably, the mass percentage of Ga contained in the GaIn alloy is 75%, because when Ga is too much or too little, Ga or In will precipitate at room temperature, causing waste.
[0023] Preferably, the heating temperature for preparing the GaIn alloy is 300° C., so that Ga is in liquid state and synthesizes the GaIn alloy with In.
[0024] Preferably, the positive electrode active material is a mixture of LiCoO2 positive electrode active material and LiFePO4 positive electrode active material.
[0025] Preferably, the mass ratio of the liquid second Ga-based alloy to the negative electrode copper foil is 2:1; the mass of the positive electrode active material is 6 times the mass of the liquid second Ga-based alloy; the mass ratio of the LiCoO2 positive electrode active material to the LiFePO4 positive electrode active material is 1:1.
[0026] Preferably, the LiCoO2 positive electrode active material is prepared by the following method: separating the positive electrode sheet from the waste LiCoO2 lithium-ion battery, and then immersing it in a liquid first Ga-based alloy to separate the aluminum foil from the positive electrode material, and calcining the separated positive electrode material to obtain the LiCoO2 positive electrode active material.
[0027] Preferably, the LiFePO4 positive electrode active material is prepared by the following method: separating the positive electrode sheet from the waste LiFePO4 lithium-ion battery, and then immersing it in a liquid first Ga-based alloy to separate the aluminum foil from the positive electrode material, and calcining the separated positive electrode material to obtain the LiFePO4 positive electrode active material.
[0028] Preferably, the pulse heating conditions are: at 1500° C., pulse heating for 200 ms, added 5 to 10 times, with an interval of 1000 ms each time.
[0029] The present invention uses positive electrode active materials as raw materials, regenerates to prepare regenerated positive electrode plates, and then assembles to prepare regenerated lithium-ion batteries, thereby realizing the reuse of positive electrode active materials.
[0030] Preferably, the specific method for preparing the regenerated lithium ion battery is: Add lithium carbonate to the positive electrode active material and calcine it to obtain a regenerated positive electrode material; use the regenerated positive electrode material as the positive electrode active material to prepare a regenerated positive electrode plate; assemble the negative electrode plate, the diaphragm material, the electrolyte and the regenerated positive electrode plate in sequence to obtain a regenerated lithium-ion battery.
[0031] Preferably, the regenerated positive electrode plate is prepared by the following method: S1. Add lithium carbonate to the positive electrode active material, calcine at 800° C. for 12 hours to achieve regeneration of the electrode material to obtain a regenerated electrode material; wherein the molar amount of the lithium carbonate is 10% of the molar amount of the positive electrode active material.
[0032] S2. Mix the regenerated electrode material, conductive carbon black and polyvinylidene fluoride to obtain an active slurry; wherein the mass ratio of the regenerated electrode material, conductive carbon black and polyvinylidene fluoride is 8:1:1.
[0033] S3, coating the active slurry on a current collector, and drying it to form an active material layer on the current collector to obtain a regenerated positive electrode sheet.
[0034] It should be noted that lithium carbonate is added to the positive electrode active material, and the metal oxide that has been delithiated in the positive electrode active material reacts with lithium carbonate by heating to restore the original composition and performance of the positive electrode active material. In addition, under the action of high temperature, some harmful substances such as electrolyte residues and impurities are decomposed or volatilized; at the same time, high temperature can also promote the reconstruction of the crystal structure of the positive electrode active material, making it more orderly, thereby improving the electrochemical performance of the regenerated lithium-ion battery.
[0035] Preferably, the current collector is aluminum foil.
[0036] Preferably, the drying temperature is 60°C and the drying time is 6 hours.
[0037] Preferably, the negative electrode plate is a lithium plate.
[0038] Preferably, the solute in the electrolyte is 1 mol / L lithium hexafluorophosphate; the solvent in the electrolyte is dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate, and the volume ratio is 1:1:1.
[0039] Compared with the prior art, the present invention has the following technical effects: 1. The present invention separates positive electrode sheets and negative copper foil from waste lithium-ion batteries; the first Ga-based alloy can maintain liquid state at room temperature and the first Ga-based alloy has high wettability to aluminum foil, so as to achieve rapid, pollution-free and low-energy separation of aluminum foil and positive electrode active material layer. At the same time, the mass percentage of Ga contained in the liquid first Ga-based alloy is 85% to 90%, which avoids the precipitation of Ga at room temperature and affects the effective separation of aluminum foil and positive electrode active material layer. There is no aluminum residue in the positive electrode active material separated by the present invention, and the separation method has little effect on the positive electrode material itself, and can well maintain its structural integrity.
[0040] 2. The present invention can utilize the separated positive electrode active material to prepare a regenerated lithium-ion battery; in addition, the positive electrode active material can be combined with the negative electrode copper foil and the second Ga-based alloy to prepare a high-entropy alloy nanoparticle catalyst, thereby broadening the application of positive electrode plates and negative electrode copper foils in waste lithium-ion batteries.
[0041] 3. The separation method of the present invention can realize the reusable utilization of the liquid first Ga-based alloy. Specifically, water is added to the liquid first Ga-based alloy after the reaction, and the aluminum in the liquid first Ga-based alloy reacts quickly with water to generate solid aluminum oxide, so that the liquid first Ga-based alloy can be separated, thereby realizing the reusable utilization of the liquid first Ga-based alloy.
[0042] 4. The high entropy alloy nanoparticle catalyst prepared by the present invention produces NO3 - The reduction reaction of nitrate ion can be carried out, and the Faradaic efficiency of catalyzing nitrate reduction at a potential of -1.4V reaches 92.1%. At the same time, the high entropy alloy nanoparticle catalyst prepared by the present invention has good chemical stability and anti-degradation properties. The present invention realizes efficient utilization of resources by recycling waste lithium ion battery materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The figure shows the change of Al content in GaSn alloy during the separation of positive electrode materials in Example 1.
[0044] Figure 2 To reuse the separation time and separation efficiency of the recovered GaSn alloy and the positive electrode sheet.
[0045] Figure 3 This is the inductively coupled plasma test mass spectrum of GaSn alloy.
[0046] Figure 4 This is the inductively coupled plasma test mass spectrum of the recovered GaSn alloy in Example 1.
[0047] Figure 5 X-ray diffraction patterns of the lithium-ion batteries prepared in Example 1 and Comparative Example 3.
[0048] Figure 6 This is the X-ray diffraction pattern of the LiFePO4 positive electrode active material separated in Comparative Example 1.
[0049] Figure 7 This is the X-ray diffraction pattern of the LiCoO2 positive electrode active material separated in Comparative Example 2.
[0050] Figure 8 This is a comparison chart of the long cycle performance of the lithium ion batteries prepared in Example 1 and Comparative Example 3.
[0051] Fig. 9 Rate test of the lithium ion batteries prepared in Example 1 and Comparative Example 3.
[0052] Fig.10 This is the linear sweep voltammetric curve of nitrate reduction of the high entropy alloy nanoparticle catalyst prepared in Example 1.
[0053] Fig.11 The Faradaic efficiency of the high entropy alloy nanoparticle catalyst prepared in Example 1 for catalyzing nitrate reduction at different potentials.
[0054] Fig.12 The cyclic voltammetric stability of the high entropy alloy nanoparticles prepared in Example 1 for 100 cycles of anthraquinone-2,7-disulfonic acid disodium catalysis was compared with that of the original carbon paper. DETAILED DESCRIPTION
[0055] As described in the background technology, the separation methods of aluminum foil and positive electrode active material layer mainly include heat treatment method, organic solvent dissolution method and chemical corrosion method of aluminum foil with mineral acid. The heat treatment method decomposes the binder at high temperature to reduce the bonding force between the active material particles, thereby weakening the adhesion between the active material layer and the aluminum foil, and realizing the separation of the positive electrode active material and the aluminum foil. The organic solvent dissolution method is to treat the positive electrode sheet with an organic solvent with good solubility so that the positive electrode active material falls off the aluminum foil; wherein the organic solvent includes N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide. The chemical corrosion method of aluminum foil with mineral acid is to use mineral acid to dissolve the aluminum foil to realize the rapid separation of the aluminum foil and the active material.
[0056] Although the heat treatment method is simple to operate, it has high energy consumption and releases harmful gases such as hydrogen fluoride, phosphorus oxides and other toxic compounds, and introduces a large amount of aluminum residues into the recovered active materials. The organic solvents in the organic solvent dissolution method include N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide. These organic solvents can effectively dissolve the polyvinylidene fluoride binder commonly used in positive electrode sheets. However, since the solubility of polyvinylidene fluoride in these solvents is limited, usually 5wt% to 10wt%, there are still aluminum residues in the active materials. During the chemical corrosion of aluminum foil by mineral acid, since the mineral acid will also react with the positive active material, the concentration and dosage of the mineral acid must be controlled to avoid corrosion of the positive active material; at the same time, the mineral acid cannot react completely with the aluminum foil, resulting in aluminum residues in the positive active material.
[0057] The above separation methods inevitably introduce aluminum residues into the separated positive electrode active materials, which will increase the difficulty of the subsequent recycling process.
[0058] The present invention develops a method for separating embrittled aluminum foil and positive electrode active material based on a liquid first Ga-based alloy. The aluminum foil and the aluminum oxide protective layer on its surface are corroded by Ga atoms in the first Ga-based alloy, thereby achieving rapid, pollution-free and low-energy stripping of the aluminum foil and the positive electrode active material layer in waste lithium-ion batteries, and no aluminum residue is left in the separated positive electrode active material.
[0059] The present invention utilizes the positive electrode active material separated by the above-mentioned separation method of waste lithium-ion batteries; preferably, the positive electrode active material is LiCoO2 positive electrode active material, LiFePO4 positive electrode active material, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 positive electrode active material or Li2Mn2O4 positive electrode active material.
[0060] On the basis of the positive electrode active material, the present invention combines the negative electrode copper foil, the positive electrode active material and the liquid second Ga-based alloy, and proposes a synthesis method of a high entropy alloy nanoparticle catalyst, aiming to achieve efficient utilization of resources by recycling waste lithium-ion battery materials.
[0061] High entropy alloy nanoparticle catalysts have a high specific surface area and unique catalytic activity, thus playing an important role in the fields of organic flow battery catalysis and nitrate reduction catalysis. Through this method, the present invention can recycle waste battery materials, which not only reduces the environmental burden of electronic waste, but also provides a new way for the green synthesis of catalysts.
[0062] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments.
[0063] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.
[0064] Example 1 This embodiment provides a method for recycling and reusing waste lithium-ion batteries.
[0065] Separation of positive electrode active materials: S1. Soak the used NMC333 ternary lithium-ion battery in 500 mL of 5 wt% NaCl solution for 24 h to fully discharge it; then manually disassemble the discharged lithium-ion battery to obtain the positive electrode strip, and put it into a fume hood to dry for later use.
[0066] S2. Under vacuum conditions, Ga and Sn were mixed in a mass ratio of 87.5:12.5, heated and stirred at 300°C for 24 hours to obtain a GaSn alloy.
[0067] S3. Cut the positive electrode strip into 1 cm×1 cm positive electrode sheets, and immerse them in 10 mL of GaSn alloy for 30 min to obtain a mixture.
[0068] S4. Separate the positive electrode material from the mixture by suction filtration to obtain the positive electrode material; wherein the filter membrane used for suction filtration is a nylon filter membrane, and the pore size of the filter membrane is 20 μm.
[0069] S5. Add 20 ml of water to the separated mixture and react for 10 minutes. Centrifuge at 8000 rpm for 5 minutes and collect the filtrate to recover the GaSn alloy.
[0070] S6. Place the positive electrode material in a muffle furnace and calcine at 600°C for 5 hours to obtain a positive electrode active material. The positive electrode active material is LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2.
[0071] Preparation of regenerated lithium-ion batteries: S1. Add lithium carbonate to the positive electrode active material, calcine at 800° C. for 12 hours to achieve regeneration of the electrode material to obtain a regenerated electrode material; wherein the molar amount of the lithium carbonate is 10% of the molar amount of the positive electrode active material.
[0072] S2. Add the regenerated electrode material, conductive carbon black and polyvinylidene fluoride into a mortar in a mass ratio of 8:1:1, grind and mix until it becomes viscous to obtain an active slurry.
[0073] S3. Coat the active slurry on aluminum foil with a thickness of 10 μm, and dry it in a vacuum oven at 60°C for 6 h to obtain a positive electrode sheet.
[0074] S4. In a glove box where the oxygen and water contents are both lower than 0.1 ppm, lithium sheets as negative electrode sheets, diaphragm materials, electrolyte of model LB-002, positive electrode sheets and CR2032 battery shells are assembled in sequence to produce regenerated lithium-ion batteries, recorded as regenerated NMC batteries.
[0075] Preparation of high entropy alloy nanoparticle catalysts: S1. Soak the used NMC333 ternary lithium-ion battery in 500 mL of 5 wt% NaCl solution for 24 h to fully discharge it; then manually disassemble the discharged lithium-ion battery to obtain the negative copper foil, which is placed in a fume hood to dry for later use.
[0076] S2. Under vacuum conditions, Ga, In and negative electrode copper foil are mixed in a mass ratio of 75:25:50, heated and stirred at 300°C for 24 hours to obtain a GaInCu alloy.
[0077] S3. Add 10 ml of ethanol to the GaInCu alloy, and use a cell crusher set at 300 W to crush for 3 hours to obtain a GaInCu nanoparticle solution.
[0078] S4. The LiFePO4 positive electrode active material separated in Comparative Example 1 and the LiCoO2 positive electrode active material separated in Comparative Example 2 are sequentially added to the nanoparticle solution and ultrasonicated for 5 minutes; wherein the mass of the LiCoO2 positive electrode active material is three times the total mass of Ga and In, and the mass of the LiFePO4 positive electrode active material is three times the total mass of Ga and In, to obtain a precursor solution.
[0079] S5. Drop the precursor solution on 3 cm × 1 cm carbon paper, and pulse heat it at 1500°C in a vacuum environment, with each heating lasting 200 ms and an interval of 1000 ms. Heat it five times to obtain a high entropy alloy nanoparticle catalyst, recorded as GaInCuFeCo.
[0080] Comparative Example 1 This embodiment provides a method for separating positive electrode active materials of waste lithium-ion batteries.
[0081] S1. Soak the used LFP18650 lithium-ion battery in 500 mL of 5 wt% NaCl solution for 24 h to fully discharge it. Then manually disassemble the discharged lithium-ion battery to obtain the positive electrode strip, which is placed in a fume hood to dry for later use.
[0082] S2. Under vacuum conditions, Ga and Sn were mixed in a mass ratio of 87.5:12.5, heated and stirred at 300°C for 24 hours to obtain a GaSn alloy.
[0083] S3. Cut the positive electrode strip into 1 cm×1 cm positive electrode sheets, and immerse them in 10 mL of GaSn alloy for 30 min to obtain a mixture.
[0084] S4. Separate the positive electrode material from the mixture by suction filtration to obtain the positive electrode material; wherein the filter membrane used for suction filtration is a nylon filter membrane, and the pore size of the filter membrane is 20 μm.
[0085] S5. Add 20 ml of water to the separated mixture and react for 10 minutes. Centrifuge at 8000 rpm for 5 minutes and collect the filtrate to recover the GaSn alloy.
[0086] S6. Place the positive electrode material in a muffle furnace and calcine at 600° C. for 5 h to obtain LiFePO4 positive electrode active material.
[0087] Comparative Example 2 This comparative example provides a method for separating positive electrode active materials of waste lithium-ion batteries.
[0088] S1. Soak the used R747 lithium-ion battery in 500 mL of 5 wt% NaCl solution for 24 h to fully discharge it; then manually disassemble the discharged lithium-ion battery to obtain the positive electrode strip, and put it into a fume hood to dry for later use.
[0089] S2. Under vacuum conditions, Ga and Sn were mixed in a mass ratio of 87.5:12.5, heated and stirred at 300°C for 24 hours to obtain a GaSn alloy.
[0090] S3. Cut the positive electrode strip into 1 cm×1 cm positive electrode sheets, and immerse them in 10 mL of GaSn alloy for 30 min to obtain a mixture.
[0091] S4. Separate the positive electrode material from the mixture by suction filtration to obtain the positive electrode material; wherein the filter membrane used for suction filtration is a nylon filter membrane, and the pore size of the filter membrane is 20 μm.
[0092] S5. Add 20 ml of water to the separated mixture and react for 10 minutes. Centrifuge at 8000 rpm for 5 minutes and collect the filtrate as the recovered GaSn alloy.
[0093] S6. Place the positive electrode material in a muffle furnace and calcine at 600° C. for 5 h to obtain LiCoO2 positive electrode active material.
[0094] Comparative Example 3 This comparative example provides a method for preparing a lithium ion battery.
[0095] S1. Add the positive electrode active material prepared in Example 1, conductive carbon black and polyvinylidene fluoride into a mortar in a mass ratio of 8:1:1, grind and mix until viscous, and obtain an active slurry.
[0096] S2. The active slurry was coated on aluminum foil with a thickness of 10 μm, and dried in a vacuum oven at 60°C for 6 h to obtain a positive electrode sheet.
[0097] S3. In a glove box where the oxygen and water contents are both lower than 0.1 ppm, a lithium sheet as a negative electrode sheet, a diaphragm material, an electrolyte of model LB-002 and a CR2032 battery shell are assembled in sequence to produce a lithium-ion battery, which is recorded as an NMC battery.
[0098] Experimental testing 1. Separate testing.
[0099] The present invention adds water to the reacted GaSn alloy to react and obtains the recovered GaSn alloy; the recovered GaSn alloy is separated for the first time to obtain the reacted GaSn alloy, which is recorded as the first cycle. This is repeated five times, and the separation time and separation efficiency in each cycle are recorded respectively.
[0100] like Figure 1 As shown, the positive electrode plate is immersed in the GaSn alloy for reaction, and the reaction is almost complete in 30 minutes. Therefore, in order to ensure that the aluminum foil in the positive electrode plate and the GaSn alloy react completely, the immersion time is preferably greater than 30 minutes, and more preferably, the immersion time is 30 minutes to 35 minutes.
[0101] like Figure 2 As shown, the recovered GaSn alloy and the aluminum foil in the positive electrode sheet can react in multiple cycles and separate the positive electrode active material; and the separation time in each cycle is stable at 30 minutes, and the separation efficiency is always stable at more than 99%. This shows that the present invention can achieve rapid, pollution-free and low-energy separation of aluminum foil and positive electrode active material layer through liquid GaSn alloy. In addition, the liquid GaSn alloy can be reused.
[0102] 2. Inductively coupled plasma testing.
[0103] like Figure 3 As shown, the GaSn alloy shows Ga, Sn and Al elements, the Ga content is 87.50293wt%, the Sn content is 12.4517wt%, and the Al content is 9.43376E -4 wt%.
[0104] like Figure 4 As shown, the recycled GaSn alloy shows Ga element, Sn element and Al element; the content of Ga element is 87.5372wt%, and the content of Sn element is 12.4604wt%.
[0105] and Figure 3 By comparison, the element composition of the recycled GaSn alloy is basically the same as that of the GaSn alloy before the reaction, and the contents of Ga and Sn are also the same. This shows that after the GaSn alloy and the positive electrode material are reacted and separated, the Ga and Sn elements in the GaSn alloy are not lost in the reaction and separation, and the obtained positive electrode active material is not dissolved, and there is no Al residue in the recycled GaSn alloy.
[0106] 3. X-ray diffraction analysis.
[0107] like Figure 5As shown, by comparing the diffraction peaks of the X-ray diffraction patterns of the NMC battery prepared in Comparative Example 3 and the regenerated NMC battery prepared in Example 1, after being repaired with lithium carbonate, the impurity peak of the regenerated lithium-ion battery disappears, and the signal of the diffraction peak is enhanced; the lattice defects in the NMC battery are repaired, the crystallinity is significantly improved, and it is consistent with the standard spectrum. This shows that the NMC battery can be repaired by lithium carbonate to obtain a regenerated lithium-ion battery. At the same time, there is no diffraction peak of aluminum atoms in the diffraction peak of the regenerated lithium-ion battery, indicating that there is no aluminum residue in the positive active material separated by the present invention.
[0108] like Figure 6 As shown, the characteristic peaks of the X-ray diffraction pattern are consistent with the standard card, proving that the separated positive electrode active material is LiFePO4.
[0109] like Figure 7 As shown, the characteristic peaks of the X-ray diffraction pattern are consistent with the standard card, proving that the separated positive electrode active material is LiCoO2.
[0110] 4. Electrochemical testing.
[0111] The present invention uses a Xinwei battery tester to perform electrochemical testing, and evaluates the cycle stability, rate performance and efficiency change of the battery through charge and discharge curve analysis to evaluate the performance of the battery.
[0112] In the cyclic charge and discharge test, the battery was tested at a rate of 0.2C for 100 cycles of constant current and constant voltage charging and constant current discharge cycles. In the rate test, the battery was tested at charge and discharge rates of 0.1C, 0.2C, 0.5C, 1C and 2C, and the specific capacity index of the battery at different rates was recorded. All tests were carried out at room temperature.
[0113] like Figure 8 As shown, compared with the NMC battery prepared without lithium carbonate repair, the regenerated NMC battery repaired with lithium carbonate can still maintain a specific capacity of 140 mAh / g after 100 charge and discharge cycles.
[0114] like Fig. 9 As shown, compared with NMC batteries, the recycled NMC batteries also exhibited excellent rate performance at different rates, proving the successful recycling of spent lithium-ion batteries.
[0115] 5. Catalytic test.
[0116] The present invention uses an electrolytic cell and a three-electrode system to measure the linear sweep voltammetry curve of the reaction; wherein the working electrode is the carbon paper where the catalytic product is located, cut into 1cm×1cm, the reference electrode is an Ag / AgCl electrode, and the counter electrode is a platinum mesh electrode. When measuring the linear sweep voltammetry, a K2SO4 electrolyte with a concentration of 0.5M, a KNO3 mixed electrolyte with a concentration of 0.1M and a K2SO4 mixed electrolyte with a concentration of 0.5M are selected for comparative testing. The current response is recorded in the range of 0V to -1.7V at a scanning rate of 10mV / s to analyze the starting potential of nitrate reduction and the catalytic activity.
[0117] like Fig.10 As shown in the figure, after adding KNO3, the linear sweep voltammetry produces an obvious change in current density, indicating that the high entropy alloy nanoparticle catalyst prepared by the present invention has NO3 - reduction reaction.
[0118] The Faraday efficiency is usually determined by constant potential electrolysis, using a 0.5M K2SO4 electrolyte or a mixed electrolyte of 0.5M K2SO4 and 0.1M KNO3, and electrolyzing for 1 hour at potentials of -1.2V, -1.3V, -1.4V, -1.5V, -1.6V and -1.7V, respectively, and calculating the Faraday efficiency by the indophenol blue ultraviolet colorimetric method. In the indophenol blue ultraviolet colorimetric method, 5ml of the reaction solution is diluted 100 times to ensure that the absorption wavelength meets the range, and 2ml of 1M sodium hydroxide solution containing 5wt% salicylic acid and 5wt% sodium citrate, 1ml of 0.05M sodium hypochlorite solution and 0.2ml of 1wt% nitrosoferric dihydrate solution are added in sequence, and after standing for 2 hours, a UV-visible spectrophotometer is used to measure the ammonium radical concentration at a wavelength of 660nm, and the Faraday efficiency is calculated by the ammonium radical concentration.
[0119] like Fig.11 As shown, the Faraday efficiency of the high entropy alloy nanoparticle catalyst prepared in Example 1 for catalyzing nitrate reduction at a potential of -1.4 V reached 92.1%.
[0120] The high entropy alloy nanoparticle catalyst catalyzed the anthraquinone-2,7-disulfonic acid disodium using the same electrode, and the electrolyte was 10mM anthraquinone-2,7-disulfonic acid disodium, 0.1M H2SO4 and 1M NH4CL for testing. The current response was recorded at a scan rate of 10mV / s in the range of 0.1V to -0.6V for 100 cycles to explore the stability of the catalytic anthraquinone-2,7-disulfonic acid disodium.
[0121] like Fig.12As shown, the high entropy alloy nanoparticle catalyst prepared in Example 1 catalyzes disodium anthraquinone-2,7-disulfonate, and the current density increases significantly, especially at the oxidation peak and reduction peak. The high entropy alloy nanoparticle catalyst increases the redox reaction rate of disodium anthraquinone-2,7-disulfonate, showing a high catalytic activity; at the same time, the curve shape under the conditions of the high entropy alloy nanoparticle catalyst remains symmetrical and regular after 100 cycles.
[0122] This indicates that the high entropy alloy nanoparticle catalyst prepared by the present invention has good chemical stability and degradation resistance.
[0123] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments, and these changes and modifications all fall within the scope of the present invention.
[0124] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the equivalent technology of the present invention, the present invention is also intended to include these modifications and variations.
Claims
1. A method for recycling waste lithium-ion batteries, characterized in that: The following steps are involved: Separate the positive electrode sheet and negative electrode copper foil from waste lithium-ion batteries; The separated positive electrode sheet is immersed in a liquid first Ga-based alloy to separate the aluminum foil from the positive electrode material, and the separated positive electrode material is calcined to obtain a positive electrode active material; the liquid first Ga-based alloy is a GaSn alloy; the mass percentage of Ga contained in the liquid first Ga-based alloy is 85% to 90%; Using positive electrode active materials as raw materials, regenerating to prepare regenerated positive electrode sheets, and then assembling to prepare regenerated lithium-ion batteries; Alternatively, a high entropy alloy nanoparticle catalyst is prepared using negative electrode copper foil, positive electrode active material and a liquid second Ga-based alloy as raw materials; the liquid second Ga-based alloy is a GaIn alloy.
2. The method for recycling waste lithium-ion batteries according to claim 1, characterized in that: The specific method for preparing a regenerated lithium-ion battery is: The positive electrode active material is mixed with lithium carbonate and calcined to obtain a regenerated positive electrode material; the regenerated positive electrode material is used as the positive electrode active material to prepare a regenerated positive electrode plate; the negative electrode plate, the diaphragm material, the electrolyte and the regenerated positive electrode plate are assembled in sequence to obtain a regenerated lithium-ion battery.
3. The method for recycling waste lithium-ion batteries according to claim 1, characterized in that: The specific method for preparing high entropy alloy nanoparticle catalyst is: The negative electrode copper foil and the liquid second Ga-based alloy are dissolved in a solvent and crushed to obtain a nanoparticle solution; the nanoparticle solution is evenly mixed with the positive electrode active material to obtain a precursor solution; the precursor solution is placed on carbon paper and pulse-heated in a vacuum environment to obtain a high entropy alloy nanoparticle catalyst; The positive electrode active material is a mixture of LiCoO2 positive electrode active material and LiFePO4 positive electrode active material.
4. The method for recycling waste lithium-ion batteries according to claim 3, characterized in that: The LiCoO2 positive electrode active material is prepared by the following method: Separating a positive electrode sheet from a waste LiCoO2 lithium-ion battery, and then immersing the sheet in a liquid first Ga-based alloy to separate the aluminum foil from the positive electrode material, and calcining the separated positive electrode material to obtain a LiCoO2 positive electrode active material; The LiFePO4 positive electrode active material is prepared by the following method: The positive electrode sheet is separated from the waste LiFePO4 lithium-ion battery, and then immersed in a liquid first Ga-based alloy to separate the aluminum foil from the positive electrode material, and the separated positive electrode material is calcined to obtain the LiFePO4 positive electrode active material.
5. The method for recycling waste lithium-ion batteries according to claim 1, characterized in that: The GaSn alloy is prepared by the following method: Ga and Sn are used as raw materials, Ga and Sn are mixed, and then heated under vacuum conditions to obtain a GaSn alloy; the heating temperature is 300°C.
6. The method for recycling waste lithium-ion batteries according to claim 1, characterized in that: The calcination temperature is 600° C. and the calcination time is 4 h to 6 h.
7. The method for recycling waste lithium-ion batteries according to claim 3, characterized in that: The mass ratio of the liquid second Ga-based alloy to the negative electrode copper foil is 2:1; The mass ratio of the LiCoO2 positive electrode active material to the LiFePO4 positive electrode active material is 1:1; The mass of the positive electrode active material is 6 times the mass of the liquid second Ga-based alloy.
8. The method for recycling waste lithium-ion batteries according to claim 1, characterized in that: The mass percentage of Ga contained in the GaIn alloy is 70% to 80%.
9. The method for recycling waste lithium-ion batteries according to claim 1, characterized in that: The regenerated positive electrode plate is prepared by the following method: The positive electrode active material is mixed with lithium carbonate, and then calcined at 800°C for 12 hours to achieve the regeneration of the electrode material to obtain a regenerated electrode material; the regenerated electrode material, conductive carbon black and polyvinylidene fluoride are mixed to obtain an active slurry; wherein the mass ratio of the regenerated electrode material, conductive carbon black and polyvinylidene fluoride is 8:1:1; The active slurry is coated on a current collector and dried to form an active material layer on the current collector to obtain a regenerated positive electrode sheet.
10. The method for recycling waste lithium-ion batteries according to claim 9, characterized in that: The molar amount of lithium carbonate is 10% of the molar amount of the positive electrode active material.
Citation Information
Patent Citations
Method for recycling and reusing positive electrode of waste lithium ion battery
CN115140785A
Waste ternary lithium ion battery positive electrode material recovery method based on sodium sulfate electrolysis
CN117458021A
Recovery method of nickel cobalt lithium manganate positive plate
CN118943545A